Retinoblastoma (RB1) gene product expression in breast carcinoma. Correlation with Ki-67 growth fraction and biopathological profile. Issue 11 (November 1998) - Ceccarelli, C; Santini, D; Chieco, P; Taffurelli, M; Gamberini, M; Pileri, S A; Marrano, D
Abstract : AIMS: To investigate the expression of retinoblastoma protein (pRb) in invasive breast tumours and compare its expression with the major biopathological prognostic indicators to identify more aggressive subgroups. MATERIAL: Archival paraffin embedded tissues from 153 consecutive primary breast carcinomas. METHODS: pRb, Ki-67, and oestrogen receptor/progesterone receptor proteins were identified by immunohistochemistry and score values were recorded by image cytometric analysis; p53 and EGFr expression was also evaluated. RESULTS: pRb scores correlated strongly with proliferation activity as determined by Ki-67 staining. Positive relations were also observed between pRb scores, tumour size, nuclear and histological grade, and oestrogen receptor/progesterone receptor content, while abnormal p53 accumulation was not associated with pRb expression. Among the high proliferating carcinomas it was possible to identify 13 cases with loss of pRb expression. CONCLUSIONS: pRb expression paralleled proliferative activity in the majority of breast carcinomas examined, suggesting that in these cases the protein behaves normally in regulating the cell cycle. Conversely in cases with loss of pRb immunostaining, the combined expression of specific highly aggressive factors (EGFr and p53 expression, oestrogen receptor/progesterone receptor negative status, and high K67) seems to characterise a more aggressive phenotype showing growth advantage and cellular "progression" rather than significant nodal involvement.